Varia Americana and Race - Eglinton, James (Journal of reformed theology, 2017)
This article explores the place of African Americans in the account of Abraham Kuyper’s 1898 American séjour found in his untranslated text Varia Americana. Utilizing Wellman’s Portraits of White Racism, its working definition of racism includes both intentional and unintentional acts that support a prejudicial racial status quo. In that light, Kuyper’s text is read as intentionally critiquing American society as racist, while also unintentionally furthering the narrative that maintained the racism he wished to condemn. As such, the article aims to prompt more nuanced engagement with the ‘deep logic’ of Kuyper’s thought, in order to aid his later inheritors in their task of reading Kuyper against himself on the topic of race.